The longitudinal study of obesity prevalence in different socio-economic status for school children: a case study of obesity prevalence for school children in antalya region - PINAR, SALİH; PINAR, YELİZ (ELSEVIER SCIENCE BV, 2012)
Purpose of Study: to investigate the obesity prevalence among school children in accordance with their gender and socio-economic levels during one year period. Four schools were chosen in accordance with their social-economic levels determined by the Ministry of National Education Directorate in Antalya for this study. Descriptive data were calculated for all variables. BMI was computed as kg/m(2). Skinfold thickness (triceps, biceps, subscapula and suprailliac) variables were measured to calculate fat (%) during one year for 7-8 years old school children. Each measurement was taken at the beginning of fall semester. Repeated measurements ANOVA and independent t test were used for statistical analyses. Girls had higher fat percentages than boys (p<.01). Students with high socio-economic status had higher BMI, fat (%), and body weight than students with low socio-economic status (p<.01). Except fat (%), all variables significantly increased during one year period. Recent studies showed higher child obesity prevalence in developing countries compared to the developed countries. However, the same situation was not observed for Turkey. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: body fat (%); BMI; socio-economic status; children; FFM; BODY-MASS INDEX; LIFE-STYLE; ADOLESCENTS; OVERWEIGHT